Where safety culture meets national culture: the how and why of the China Airlines CI-611 accident - Li, Wen-Chin; Harris, Don (Ashgate Publishing, 2006)
There has been a great deal of research regarding the relationship between national culture and aviation safety. Soeters and Boer (2000) suggested that safety was enhanced when national culture was more individualistic in nature.Morley and Harris (2006) developed an open system model of safety culture – the Ripple Model. This model identified three threads running throughout the personnel within (and without) an organisation, irrespective of their level and role. These were labelled ‘Concerns’, ‘Influences’ and ‘Actions’ and were evident in line personnel; middle management; senior management; the industry regulator; government and society as a whole. Concerns were associated with threats to the needs of the individual and worries about meeting the requirements placed on them by others. Influences were concerned with the factors that dictated the methods by which safety needs could be accomplished. Actions described the behaviours that directly impacted upon safety, in either a positive or negative manner. In this model the authors argued that elements outside an organization have a profound effect on safety culture. The boundaries for the conceptualisation of safety culture must be extended beyond the organisation if a comprehensive model of the evolution of safety culture is to be developed.
Keywords: Accident Investigation; Human Errors; Ripple Model; Safety Culture